2016
DOI: 10.1177/1077801216638766
|View full text |Cite
|
Sign up to set email alerts
|

The Girl Is Mine

Abstract: Intimate partner violence (IPV) and sex work have been primarily constructed as mutually exclusive phenomena within scholarly literature, though both can be situated under the umbrella of gender-based violence and traced to male sexual proprietariness. Specialized research has resulted in deeper understanding of nuanced categorizations of sub-phenomena within both IPV and sex work, with parallel constructions along a spectrum of increasing danger. However, the scholarly construction of these continua as parall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 96 publications
4
11
0
Order By: Relevance
“…In addition to the association between TGBs and mental health outcomes, an important finding was the association found between TGBs and IPV. These findings are consistent with previous research on the relevance of TGBs and their consequences in IPV [ 76 ]. Past research showed that IPV could be understood as a bidirectional phenomenon in which both parties use violence and/or abusive behaviors against one another [ 41 , 73 ].…”
Section: Discussionsupporting
confidence: 93%
“…In addition to the association between TGBs and mental health outcomes, an important finding was the association found between TGBs and IPV. These findings are consistent with previous research on the relevance of TGBs and their consequences in IPV [ 76 ]. Past research showed that IPV could be understood as a bidirectional phenomenon in which both parties use violence and/or abusive behaviors against one another [ 41 , 73 ].…”
Section: Discussionsupporting
confidence: 93%
“…In addition to the association between TGBs and mental health outcomes, an important nding was the association found between TGBs and IPV. These ndings are consistent with previous research on the relevance of TGBs and their consequences in IPV (Thaller & Cimino, 2017). Past research showed that IPV could be understood as a bidirectional phenomenon in which both parties use violence and/or abusive behaviors against one another (Langhinrichsen-Rohling et al, 2012; Sommer et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…Thus, we found multiple instances of each of the coercive control tactics described by Stark, as well as threats of abandonment, in the reports by participants in this study, showing that this framework can be applied to this population. This is critical because existing research has viewed women in prostitution as a separate category from women in the general population who experience IPV (Thaller & Cimino, 2017). The results suggest that the underlying coercion may be similar.…”
Section: Discussionmentioning
confidence: 97%
“…This study's findings also revealed that when these intimate partners eventually engaged in increasing pimp behaviors, they became physically, sexually, and emotionally violent and economically exploitive. Thus, it appears that the boundaries between intimate partner and pimp roles may be blurred, and the overlapping methods of coercion within some relationships necessitate clarification concerning coercive control patterns (Thaller & Cimino, 2017).…”
Section: Experiences Of Coercive Control In Women Exiting Prostitutionmentioning
confidence: 99%